Low-cost implementation of active noise control techniques for construction noise - Tan, Nicholas Hui Xian (Nanyang Technological University, 2024)
Noise pollution poses significant threats to human and wildlife. In a fast-developing country like Singapore where land is scarce, noise pollution stems primarily from construction noises. Current implementations to curb with the construction noises include traditional acoustic methodologies such as ear plugs, earmuffs, and noise barriers. As Singapore continues to develop further, current approaches to mitigate noise pollution due to construction noises are limited.